2017
DOI: 10.1508/cytologia.82.3
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Characteristics of the Tropical Oyster, <i>Crassostrea belcheri</i> Sowerby, 1871 (Ostreoida, Ostreidae) by Conventional and Ag-NOR Banding Techniques

Abstract: Chromosome preparation from gill tissue of the tropical oyster (Crassostera belcheri Sowerby, 1871) collected from an oyster farm in Kantang District, Trang Province, southern Thailand was studied by conventional staining and Ag-NOR baining techniques. The result revealed that the diploid chromosome number is 2n=20 and the fundamental number (NF) is 40. The karyotype has revealed 10 large metacentric and 10 medium metacentric chromosomes. One pair of nucleolar organizer regions (NORs) was apparent on the short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 20 publications
3
26
0
Order By: Relevance
“…Conventional staining was done using 10% Giemsa s solution for 10 min (Chooseangjaew et al 2017). Ag-NOR banding was performed (Howell and Black 1980) by applying two drops of 2% gelatin on the slides, followed with four drops of 50% silver nitrate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional staining was done using 10% Giemsa s solution for 10 min (Chooseangjaew et al 2017). Ag-NOR banding was performed (Howell and Black 1980) by applying two drops of 2% gelatin on the slides, followed with four drops of 50% silver nitrate.…”
Section: Methodsmentioning
confidence: 99%
“…The relative length (RL), the centromeric index (CI), and standard deviation (SD) of RL and CI were estimated (Chaiyasut 1989). The CI (q/p+q) between 0.50-0.59, 0.60-0.69, 0.70-0.89, and 0.90-0.99 were described as metacentric, submetacentric, acrocentric and telocentric chromosomes, respectively (Chooseangjaew et al 2017). All data were used in karyotyping and idiograming.…”
Section: Methodsmentioning
confidence: 99%
“…Mitotic chromosome preparations were made from anterior kidney after in vivo treatment using a method modified from Chen and Ebeling (1968), Gold et al (1990), Kasiroek et al (2017) and Supiwong et al (2017). The chromosomes were stained with 10% Giemsa s for 30 min (Chooseangjaew et al 2017) and identified for NORs by Ag-NOR staining technique (Howell andBlack 1980, Sangpakdee et al 2017). The length of short arm (Ls) and long arm (Ll) chromosomes were measured and the length of total arm chromosome was calculated (LT, LT=Ls+Ll).…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of their chromosome was conducted by squash technique from bone marrow and testis (Kasiroek et al 2017). The chromosomes were stained with 10% Giemsa s for 30 min (Chooseangjaew et al 2017) and identified for NORs by Ag-NOR staining (Howell andBlack 1980, Sangpakdee et al 2017). The length of short arm (Ls) and long arm (Ll) chromosome were measured and calculated for the length of total arm chromosome (LT, LT=Ls+Ll).…”
Section: Methodsmentioning
confidence: 99%
“…Relative length (RL) and centromeric index (CI) were also calculated. CI was estimated to classify the types of chromosomes according to Chaiyasut (1989) and Chooseangjaew et al (2017). All parameters were used in karyotyping and idiograming.…”
Section: Methodsmentioning
confidence: 99%